Pembuatan Gula Kelapa/Aren Guna Peningkatan Pendapatan Bumdes Argo Manik Desa Kalipelus Kebonagung Pacitan - Rahmawati Rahmawati; Siti Arifah; Edy Supriyono; Francisca Sestri Goestjahjanti; Bambang Pujiasmanto; Pringgo Widyo Laksono; Ratna Wijayanti Daniar Paramitha; Rita Noviani; Siti Nurlaela (Empowerment: Jurnal Pengabdian Masyarakat, 2023)
This Community Service activity aims to increase the capabilities of BUMDes Argo Manik in managing coconut/aren sugar production from upstream to downstream to create innovative and productive villages, and increase greening of the environment in order to support tourism and environmental preservation. The method used is the delivery of material from resource persons who are competent in their fields related to problems that exist in the community and training according to the directions of the resource persons. The result of this activity is an increase in the quality of coconut/aren sugar products that have been produced and managed by BUMDes Argo Manik in supporting the tourism potential in Kalipelus Village which in turn can improve the economy of the Kalipelus Village community. The conclusion that can be drawn from this activity is that the role of academics is needed in order to participate in providing solutions to problems that occur in society. This activity can also be input for the formation of an academic climate in tertiary institutions, especially related to the people's economy.